2021
DOI: 10.1002/jso.26773
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal therapy for synchronous bone oligometastatic NSCLC: The role of surgery

Abstract: Objectives The study aimed to assess the feasibility of radical surgical treatment for selected bone‐oligometastatic non‐small cell lung cancer (NSCLC) patients and to identify prognostic factors associated with survival. Materials and methods The clinical records of 27 patients with bone synchronous oligometastatic NSCLC were retrospectively analyzed. Results Thirteen (48.1%) bone metastases were treated by surgery and 14 (51.9%) by local radiotherapy. Eighteen (66.7%) patients underwent induction chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Bone is the most common site of distant metastasis in patients with stage IV NSCLC and has a very poor prognosis. An increasing number of clinical trials have confirmed the effectiveness and feasibility of LCT in NSCLC patients with bone oligometastasis [ 26 , 27 ]. However, there is no consensus on the exact number of metastases to define oligometastasis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bone is the most common site of distant metastasis in patients with stage IV NSCLC and has a very poor prognosis. An increasing number of clinical trials have confirmed the effectiveness and feasibility of LCT in NSCLC patients with bone oligometastasis [ 26 , 27 ]. However, there is no consensus on the exact number of metastases to define oligometastasis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a retrospective analysis involving 27 patients with synchronous bone oligometastatic NSCLC also illustrated that surgical treatment is associated with anticipated survival bene ts [27] . Our study validated these points through analysis of the SEER database, but prostate cancer and liver cancer do not align with the conclusion, which underscores the importance of personalized treatment decisions based on each cancer type and patient.…”
Section: Discussionmentioning
confidence: 99%
“…And similar survival benefit was observed in other oligometastatic NS-CLC patients involving different organs. [24] Due to the complex nature of the metastatic disease and primary tumor, patient survival could be influenced by many aspects including the overall condition of the patient, tumor load and its biological behavior, and patient response to local and systemic treatment. Patient selection is one of the factors that impede a definite conclusion, as patients who are fit for surgical treatment usually have few comorbidities and less tumor burden.…”
Section: Survival After Primary Lung Tumor Resectionmentioning
confidence: 99%